Ginger: a representative material of herb-derived exosome-like nanoparticles - Zhu, He; He, Wenxi (Frontiers in Nutrition, 2023)
Edible plant-derived exosome-like nanoparticles (PELNs) provide numerous benefits, including high yield, low cost, ethical compatibility, and multiple health benefits, which enable them to address technical constraints associated with mammalian nanoparticles. Herbs, known for their abundant bioactive components, are considered the primary source of natural medicines within the plant kingdom. Recently, a number of herbaceous sources have been investigated for the isolation and functionality of exosome-like nanoparticles (ELNs). However, they are commonly referred to as PELNs, and their distinct pharmacological properties are overlooked. In this review, these herbderived ELNs are designated as HELNs, a novel herbal product that may also exhibit superior pharmacological activity compared to other types of PELNs. Among the documented HELNs, ginger-derived exosome-like nanoparticles (GELNs) are the most extensively studied. This review employs GELNs as an exemplar to delineate the process of extraction and purification, together with their physical and biochemical characteristics and therapeutic potential. The aim of this review is to promote the development and application of HELNs, and future research is encouraged to uncover their additional properties, extending beyond those of GELNs.